‘CONTEXTUALIZING’ INTELLIGENCE IN STRATEGIC BEHAVIOUR OF INDIA TOWARDS NEPAL - 1. Dr. Arundhati Sharma, 2. Jitendra Kumar Yadav (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Applying the concept of ‘contextual intelligence’, the paper assesses the strategic behaviour of India under different leaderships and explores Nepal’s changing political contexts since the end of the civil war in November 2006 to 2020. In assessing the behaviour of different leaderships, the available resources have been presented in a defined manner and supplemented with data collected through interviews with experts in India and Nepal. The paper argues that India’s strategy towards Nepal has been affected by the way different leaderships construed the changing political contexts particularly in Nepal to devise their strategies to create a favourable environment.